Reactive powder concrete-filled steel tube (RPCFT) members subjected to axial tension: Experimental study and design. (December 2020) - Lai, Zhichao; Yao, Pengyu; Huang, Wenjin; Chen, Baochun; Ying, Zheng
Highlights: Experimentally evaluates the tensile behavior of RPCFT members. Compares the tensile behavior of RPCFT, RPC, and HSS members. Compares the tensile strength of RPCFT and CFT members. Proposes design equation to estimate the tensile strength of RPCFT members. Abstract: Reactive powder concrete-filled steel tube (RPCFT) consists of rectangular or circular steel tube filled with reactive powder concrete (RPC). Currently, there is a general lack of knowledge regarding the behavior of RPCFT members subjected to axial tension. This paper addresses the knowledge gap by conducting experimental tests on 57 specimens, including 33 RPCFT specimens, 21 RPC specimens, and three hollow steel tube (HSS) specimens. The test parameters are the diameter-to-thickness ratio of the steel tube, fiber reinforcement ratio, and curing temperature. The test results indicate that the tensile strength of RPCFT members increases with increasing fiber reinforcement ratios and curing temperatures or with decreasing diameter-to-thickness ratios of the steel tube. As compared to conventional concrete-filled steel tube (CFT) members, RPCFT members have: (i) a similar tensile behavior, i.e., the steel tube has an increased tensile strength and does not have any pinching due to the interaction between the steel tube and concrete infill; and (ii) a higher tensile strength because RPC with fibers has a higher tensile strength than conventional concrete and can maintain its tensile capacity at large strains. This paper also evaluates the applicability of current design equations for estimating the axial tensile strength of RPCFT members. The evaluation indicates that the current design equations are over-conservative for RPCFT members. This paper then proposes a new design equation for estimating the axial tensile strength of RPCFT members. The accuracy of the proposed equation is confirmed by using it to predict the strength of the 33 RPCFT specimens tested in this research.